Analisis Komunikasi Wali Kota Surabaya untuk Menekan Kasus Covid-19 dalam Perspektif Sosiolinguistik - Moh Khoirul Anam; Ariza Qurrata A'yun (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2022)
This study discusses the involvement of text and social elements in producing texts used for mass communication through a sociolinguistic perspective. The purpose of this study is to elaborate on sociolinguistic factors of the Surabaya Mayor's appeal in handling Covid-19. The method used in this study is descriptive qualitative. The primary data of the research is the recorded audio of the appeal of the mayor of Surabaya. The results have revealed that the communicator uses a specific diction that aims to bring social distance closer to the communicant. Various dictions are used with the pronouns Kita/Kami, Saya, Kulo, and Jenengan. In addition, communicators also use Javanese as a form of ethnic solidarity and, in a certain part, communicators use Arabic to show aspects of religiosity.